Dexamethasone-cyclophosphamide pulse therapy outcomes comparing pemphigus vulgaris and pemphigus foliaceus groups in a Brazilian cohort study - Ludmilla Figueiredo Fontenelle; Roberto Bueno-Filho; Sebastián Vernal; Renata Delfino; Giovanna Stefanne Lópes Barbosa; Eduardo Antonio Donadi; Ana Maria Roselino (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Dexamethasone-cyclophosphamide pulse (DCP) and dexamethasone pulse (DP) have been successfully used to treat pemphigus, but DCP/DP outcomes comparing pemphigus vulgaris (PV) and pemphigus foliaceus (PF) are scarce. Objective To compare DCP/DP outcomes in a Brazilian cohort of PV and PF patients according to demographic and clinical data. Methods Retrospective analytical cohort study, reviewing medical charts of PV and PF patients (for DCP/DP Phases I‒IV consult Pasricha et al.16‒18). Results 37 PV and 41 PF patients non responsive to usual treatments were included similarly for DCP or DP therapy. Disease duration was longer among PF before DCP/DP prescription (p < 0.001); PF required a higher number of monthly pulses to acquire remission in Phase I (median 10 and 6 pulses, respectively; p = 0.005). DCP/DP outcomes were similar in both groups: remission in 37.8% of PV and 34.1% of PF after completed DCP/DP cycles following a median of 13 months (1-56 months follow-up); failure occurred in 13.5% of PV and 14.6% of PF in Phase I; relapse in 13.5% of PV and 12.2% of PF, and dropout in 27% of PV and 24.4% of PF in Phases II to IV. Mild side effects were documented. Study limitations The severity of PV and PF disease was not assessed by score indexes. Conclusions PV and PF patients presented similar DCP/DP outcomes. DCP/DP should be initiated earlier in PF patients due to the longer duration of their disease in order to decrease the number of pulses and the duration of Phase I to acquire remission.